Inhibition of glucose transport synergizes with chemical or genetic disruption of mitochondrial metabolism and suppresses TCA cycle-deficient tumors. Issue 3 (17th March 2022) - Olszewski, Kellen; Barsotti, Anthony; Feng, Xiao-Jiang; Momcilovic, Milica; Liu, Kevin G.; Kim, Ji-In; Morris, Koi; Lamarque, Christophe; Gaffney, Jack; Yu, Xuemei; Patel, Jeegar P.; Rabinowitz, Joshua D.; et al.
Summary: Efforts to target glucose metabolism in cancer have been limited by the poor potency and specificity of existing anti-glycolytic agents and a poor understanding of the glucose dependence of cancer subtypes in vivo . Here, we present an extensively characterized series of potent, orally bioavailable inhibitors of the class I glucose transporters (GLUTs). The representative compound KL-11743 specifically blocks glucose metabolism, triggering an acute collapse in NADH pools and a striking accumulation of aspartate, indicating a dramatic shift toward oxidative phosphorylation in the mitochondria. Disrupting mitochondrial metabolism via chemical inhibition of electron transport, deletion of the malate-aspartate shuttle component GOT1, or endogenous mutations in tricarboxylic acid cycle enzymes, causes synthetic lethality with KL-11743. Patient-derived xenograft models of succinate dehydrogenase A ( SDHA )-deficient cancers are specifically sensitive to KL-11743, providing direct evidence that TCA cycle-mutant tumors are vulnerable to GLUT inhibitors in vivo . Graphical abstract: Highlights: KL-11743 is a potent, bioavailable inhibitor of class I glucose transporters Glucose deprivation depletes NADH and dramatically increases aspartate levels KL-11743 synergizes with electron transport inhibitors to induce cell death Mutations in TCA cycle enzymes are synthetically lethal with KL-11743 Abstract : Olszewski et al. identify and characterize KL-11743, a small-molecule inhibitor of class I glucose transporters. KL-11743 blocks glucose uptake in vitro and in vivo, induces aspartate accumulation and increases mitochondrial metabolism. KL-11743 treatment specifically inhibits the growth of tumors with a truncated TCA cycle due to mutations inactivating succinate dehydrogenase.